Detection of absolute rotation using superfluid ⁴He - Schwab, K.; Bruckner, N.; Packard, R. (Физика низких температур, 1998)
We have developed the superfluid analog of the superconducting rf SQUID. Such a device is a
quantum mechanically based, absolute gyroscope and has been used to sense the rotation of the Earth
Our device is fabricated using silicon processing techniques and forms a planer sensing loop of superfluid
helium which couples to the applied rotation. A much more sensitive superfluid gyroscope based on the
principals demonstrated with this device, might ultimately be used to detect the precession of our local
inertial frame with respect to the fixed stars by the gravitomagnetic field of the rotating Earth. We
compare the superfluid gyroscope against two other experiments aimed at detecting this general
relativistic effect.